Anthomalachius, a new genus of soft-winged flower beetles (Coleoptera, Malachiidae: Malachiinae) - Tshernyshev, Sergei E. (Zootaxa, 2009)
A new malachiid beetle genus, Anthomalachius gen. n., is described for Clanoptilus spinosus species group. Figures of male habiti, special structures, genitalia, and a distribution map for all species are given.